An Experimental and Theoretical Study of the 1,3-Dipolar Cycloaddition of Alloxan-Derived Azomethine Ylides to Cyclopropenes - Filatov, Alexander S.; Selivanov, Stanislav I.; Shmakov, Stanislav V.; Larina, Anna G.; Boitsov, Vitali M.; Stepakov, Alexander V. (Synthesis, 2021)
A diastereoselective synthesis of biologically interesting spirobarbiturates has been achieved via [3+2] cycloaddition of alloxan-derived azomethine ylides to 3-R-1,2-diphenylcyclopropenes. With this approach, a range of spirobarbiturate-3-azabicyclo[3.1.0]hexanes and spirobarbiturate-cyclopropa[a]pyrrolizines were obtained in moderate to good yields with excellent diastereoselectivities. DFT calculations (M11 density functional theory) were carried out to shed light on the molecular mechanism of 1,3-dipolar cycloaddition of alloxan-derived azomethine ylides to cyclopropenes. The cytotoxic activity of some obtained compounds against human erythroleukemia (K562) cell line was evaluated in vitro by MTS-assay.
Keywords: 1,3-dipolar cycloaddition; azomethine ylides; cyclopropenes; alloxan; one-pot, three-component reactions; spirobarbiturates; diastereoselectivity; DFT calculations